Dependence Of Karakul Sheep's Milk Productivity on Their Udder Structure - Bekbaev Khanpolat Arislanbaevich; Kaniyazova Albina (Genius Journals, 2021)
The article presents the study of milk productivity of karakul sheep depending on the colour in the northern conditions of the Republic of Karakalpakstan. Optimal opportunities of increasing milk productivity were determined; the results of changing daily milk productivity in agedependent dynamics were given.
Keywords: Milk Productivity; Sheep Colour; Sheep Age; Semi-circular udder